DESAIN KEMASAN ICE CREAM SAYUR UNTUK PRODUK UMKM DESA DUWET KECAMATAN TUMPANG KABUPATEN MALANG - Tiara Estu Amanda; Evi Suwarni; Prima Beauty Kartikasari; Alvin Nouval; Cahyo Ramadhan Pratama; Bambang Suryanto (Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service aims to provide service in the form of an attractive healthy vegetable ice cream packaging design for MSME products Duwet Village, Malang Regency has problems, including: The abundance of vegetables in Duwet Village causes several problems, such as excess inventory that can cause price declines and farmers' losses. Therefore, food diversification products in the form of healthy vegetable ice cream were made. To attract buyers' interest, it is necessary to create an attractive ice cream packaging design. This community service activity is in the form of an attractive healthy vegetable ice cream packaging design for MSME products in Duwet Village, Malang Regency. At the same time, to overcome the problem of the abundance of vegetables that have not been used properly, food diversification, especially by creating healthy vegetable ice cream and attractive ice cream packaging designs can be a solution. It not only utilizes surplus vegetables, but also creates value-added products, supports local economies, and provides consumers with healthy food options